Study on seismic response of a new staggered story isolated structure considering SSI effect - Liu, Dewen; Li, Liping; Zhang, Yafei; Chen, Lihao; Wan, Feng; Yang, Fan (Journal of Civil Engineering and Management, 2022)
The new staggered story isolated structure is a new type of seismic isolated structure developed from base isolated structure and inter-story isolated structure. In order to explore the seismic response of the new staggered story isolated structure considering the soil-structure interaction (SSI), the model of a new staggered story isolated structure considering SSI effect is established to analyze the nonlinear dynamic time-history response under rare earthquakes, and the comparison between hard soil and soft soil was carried out. Results show that the stiffness of the new staggered story isolated structure reduced, the modal period extended and the seismic response reduced by considering the SSI effect, the softer the site soil, the more obvious those changes are. Meanwhile, the shear force and the damage of the core tube decreases, while the shear force and the damage of the frame increases, the shear force transfers from the core tube to the frame. Additionally, the energy absorption of the seismic isolated bearings at the frame reduced, the energy absorption of the seismic isolated bearings at the core tube increased, the softer the site soil, the more obvious the trend is.